Addressing the long-standing limitations of double exponential and non-rectangular hyperbolic models in quantifying light-response of electron transport rates in different photosynthetic organisms under various conditions - Ye, Zi-Piao; An, Ting; Govindjee, Govindjee; Robakowski, Piotr; Stirbet, Alexandrina; Yang, Xiao-Long; Hao, Xing-Yu; Kang, Hua-Jing; Wang, Fu-Biao (Frontiers in Plant Science, 2024)
The models used to describe the light response of electron transport rate in photosynthesis play a crucial role in determining two key parameters i.e., the maximum electron transport rate (Jmax) and the saturation light intensity (Isat). However, not all models accurately fit J–I curves, and determine the values of Jmax and Isat. Here, three models, namely the double exponential (DE) model, the non-rectangular hyperbolic (NRH) model, and a mechanistic model developed by one of the coauthors (Z-P Ye) and his coworkers (referred to as the mechanistic model), were compared in terms of their ability to fit J–I curves and estimate Jmax and Isat. Here, we apply these three models to a series of previously collected Chl a fluorescence data from seven photosynthetic organisms, grown under different conditions. Our results show that the mechanistic model performed well in describing the J–I curves, regardless of whether photoinhibition/dynamic down-regulation of photosystem II (PSII) occurs. Moreover, both Jmax and Isat estimated by this model are in very good agreement with the measured data. On the contrary, although the DE model simulates quite well the J–I curve for the species studied, it significantly overestimates both the Jmax of Amaranthus hypochondriacus and the Isat of Microcystis aeruginosa grown under NH4+-N supply. More importantly, the light intensity required to achieve the potential maximum of J (Js) estimated by this model exceeds the non-expected high value of 105 μmol photons m−2 s−1 for Triticum aestivum and A. hypochondriacus. The NRH model fails to characterize the J-I curves with dynamic down-regulation/photoinhibition for Abies alba, Oryza sativa and M. aeruginosa. In addition, this model also significantly overestimates the values of Jmax for T. aestivum at 21% O2 and A. hypochondriacus grown under normal condition, and significantly underestimates the values of Jmax for M. aeruginosa grown under NO3--N supply. Our study provides evidence that the ‘mechanistic model’ is much more suitable than both the DE and NRH models in fitting the J–I curves and in estimating the photosynthetic parameters. This is a powerful tool for studying light harvesting properties and the dynamical down-regulation of PSII/photoinhibition.